بنية الشخثية في رواية ذكرى ميلينا للكاتب محمد بوزيد - لدغم, كنيوة, شيماء حنان; زغوان, صفاء (University of El-oued, 2022)
يعالج هذا الموضوع الذي جاء تحت عنوان بنية الشخصية في رواية "ذكرى ميلينا" لمحمد بوزيد اسم العناصر الموجودة في الرواية وهي بنية الشخصية باعتبارها المحرك الرئيسي والمحور الفعال الذي تقوم عليه نجاح الرواية. ومن هذا المنطلق فقد تعددت العناصر داخل هذا العمل شاملا مفهوم الشخصية والتطرق إلى أنواعها مرورا بطرق بناء واستعراض أبعادها وعلاقتها بالمكونات السردية الأخرى إلى غاية إبراز أهميتها، كل هذا ساهم في بناء الرواية. كما عالج هذا البحث عدة أبعاد للشخصية متمثلة في الأبعاد النفسية وهي التي تساعد في سرد انفعال الشخصية والبعد الاجتماعي الذي تجلى في رصد العينات الإنسانية الفاعلة في المجتمع وأخيرا البناء الخارجي الذي يحتوي على البعد الجسماني الذي يتم من خلاله وصف الشكل الخارجي للشخصية This topic, which came under the title of the character structure in the novel "The Memory of Melina" by Mohamed Bouzid, deals with the name of the elements in the novel, which is the character's structure as the main driver and the effective axis on which the success of the novel is based. From this point of view, there were many elements within this work, including the concept of personality and addressing its types, passing through ways of building and reviewing its dimensions and its relationship with other narrative components to the point of highlighting its importance, all of this contributed to building the novel. This research also dealt with several dimensions of personality represented in the psychological dimensions, which help to narrate the personality's emotion and the social dimension that was manifested in monitoring the active human samples in society and finally the external structure that contains the physical dimension that is done by describing the external form of the personality.
Keywords: structure, personality, internal structure of personality, external structure of personality.; البنية، الشخصية، البناء الداخلي للشخصية، البناء الخارجي للشخصية.